Potensi Pemanfaatan Limbah Kelapa Sawit di PT GMM Kabupaten Halmahera Selatan sebagai Pakan Alternatif bagi Ternak Ruminansia - Gunawan, Gunawan; Utami, Sri; Lestari, Sri; Sulasmi, Sulasmi; Haryanto, Sugeng (Universitas Khairun, 2025)
This study aimed to evaluate the potential utilization of oil palm waste from PT. Gelora Mandiri Membangun (GMM) in South Halmahera as an alternative feed for ruminant livestock. Waste samples including empty fruit bunches (EFB), palm fiber, and Palm Oil Mill Effluent (POME) were collected and analyzed for their nutritional content using proximate analysis methods, followed by feeding trials on local goats. The results showed that fermented POME exhibited the highest crude protein content at 7.80%, while EFB contained 38.20% crude fiber, and palm fiber contained up to 9.20% fat. Feeding trials indicated that goats fed with diets based on fermented POME achieved an average daily weight gain (ADWG) of 91 g/head/day, only slightly lower than those fed with commercial feed (95 g/head/day). These findings suggest that, after simple processing such as fermentation, oil palm waste holds great potential as an alternative feed material without significantly reducing livestock performance. The study concludes that oil palm waste can be an efficient, economical, and environmentally friendly alternative feed source. Utilizing this waste also supports the principles of sustainable agriculture and circular economy while offering economic benefits to local communities through the integration of plantation and livestock sectors. It is recommended to develop simple waste processing technologies and foster local partnerships to optimize the utilization of these resources.